Resistivity Data Modeling for Subsurface Volcanostratigraphy Construction of Cibadak Sub-Watershed, Bogor, West Java, Indonesia. - Muhammad Kurniawan Alfadli; Undang Mardiana; Nanda Natasia; Febriwan Mohammad; Deden Zaenudin Mutaqin (UIR PRESS, 2021)
In Mt. Salak, there are six volcanic facies divided by eruption time seen from geomorphology data analysis and to identified the subsurface layer DC Resistivity method is applied. Beside resistivity, geostatistical parameters also influence the result model interpretation, so for obtain best model correlation parameters such as tilting, surfacing, variogram, grid method, and logarithmic distribution is applied. Using 18 points of acquisition data subsurface model is produce and then section model made to describe vertical resistivity distribution then correlated with facies lithology model. Based on that, produce three facies resistivity type namely: 0 – 100 Ohm.m (Low Resistivity Value) Interpreted as pyroclastic material composed as tuff and breccia that lies under lava. 100 – 300 Ohm.m (Medium Resistivity Value) Interpreted as breccia lithology type. Harder that pyroclastic material due to by this product is avalanches of lava. And >300 Ohm.m (High Resistivity Value) Interpreted as lava lithology that lies at high elevation and the hardest lithology in this area. From the model, pyroclastic layer that is modeled found at low elevation and based on the direction it described as oldest facies layer, but at the bottom of this layer lies high resistivity value that unknown product. It can be Mt. Pangrango product due to at low elevation predicted as combine area product from product of Mt. Salak and Pangrango. High resistivity value show lava lithology and lava facies located in high elevation and medium resistivity describe breccia lithology as avalanche product of lava (youngest pyroclastic facies) and found at 500 – 100 meters msl.